Copper‐Catalyzed Borocarbonylative Coupling of Internal Alkynes with Unactivated Alkyl Halides: Modular Synthesis of Tetrasubstituted β‐Borylenones - Cheng, Li‐Jie; Mankad, Neal P. (Angewandte Chemie International Edition, 2018)
Reported is a general procedure to synthesize tetrasubstituted enones, which are borylated in the β‐position, using a copper‐catalyzed four‐component coupling reaction of simple chemical feedstocks: internal alkynes, alkyl halides, bis(pinacolato)diboron (B2pin2), and CO. A broad scope of highly functionalized β‐borylated enones, a largely unknown class of organic compounds, can be accessed efficiently using this method. The synthesis of all‐carbon tetrasubstituted enones was realized by employing the β‐borylated enone unit, without purification, in a Suzuki–Miyaura coupling. The utility of the method was further demonstrated by various transformations, including halogenation, oxidation, and protodeboration, of the corresponding reduced oxaborole species to provide densely substituted allylic alcohol and ketone products. Four bits: A copper‐catalyzed four‐component coupling reaction of alkynes, alkyl halides, B2pin2, and CO enables modular synthesis of β‐borylated tetrasubstituted enones. The reaction employs readily available feedstocks and proceeds under mild reaction conditions. The utility of this method was demonstrated by various transformations of the borylated products.